Efficacy and safety of low-dose celecoxib with chemoradiation in locally advanced head-and-neck squamous cell carcinoma - Rethinesh Kumar T; Jabapriya B; Angappan P (Asian Journal of Medical Sciences, 2024)
Background: Head-and-neck squamous cell carcinoma (HNSCC) is a major cancer in India with a poor prognosis. Novel antineoplastic agents, such as selective cyclooxygenase-2 inhibitors such as celecoxib, have shown antitumor, anti-angiogenesis, and radiosensitizing effects, improving radiotherapy response in many cancers. Aims and Objectives: This study aimed to determine the efficacy and safety of low-dose celecoxib combined with concurrent chemoradiation in Locally Advanced HNSCC. Materials and Methods: A double-arm prospective randomized control study was conducted, in which 103 eligible locally advanced HNSCC patients were randomized to concurrent chemoradiotherapy 66 Gy/2 Gy/33 fractions/61/2 weeks along with Inj Cisplatin 40 mg/m2 weekly either with celecoxib 100 mg twice daily (Study Arm – 62) or placebo (Control Arm – 41). Tumor response was evaluated using response evaluation criteria in solid tumors criteria 1.1 and acute toxicities based on the radiation therapy oncology group and common terminology criteria for adverse events criteria 5.0. Results: On analysis using the Chi-square test, the complete response rate was 65.6% in the study arm compared to 44.7% in the control arm, with P=0.0441 (significant at P<0.05). The incidence of acute dermatitis and mucositis (grade ≥3) in the study and control arms was 29.3% versus 23.6%, with P=0.544 and 40% versus 37% with a P=0.782 (insignificant at P<0.05), respectively. The patients in both arms were followed up to assess late toxicities, locoregional control rate, disease-free survival, and overall survival. Conclusion: Adding low-dose daily celecoxib to concurrent chemoradiation with weekly cisplatin in locally advanced HNSCC significantly improved the clinical response rates with acceptable treatment-related toxicities.